2012
DOI: 10.1371/journal.pone.0030300
|View full text |Cite
|
Sign up to set email alerts
|

Bezielle Selectively Targets Mitochondria of Cancer Cells to Inhibit Glycolysis and OXPHOS

Abstract: Bezielle (BZL101) is a candidate oral drug that has shown promising efficacy and excellent safety in the early phase clinical trials for advanced breast cancer. Bezielle is an aqueous extract from the herb Scutellaria barbata. We have reported previously that Bezielle was selectively cytotoxic to cancer cells while sparing non-transformed cells. In tumor, but not in non-transformed cells, Bezielle induced generation of ROS and severe DNA damage followed by hyperactivation of PARP, depletion of the cellular ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…The TUNEL assay demonstrated that tumor cells do not undergo apoptosis and therefore, increased ROS generation by OXPHOS does not reach toxic levels. Based on our results and as currently stated by Whitaker-Menezes et al [57] in the context of breast cancer we assume that mitochondria are the ‘Achilles heel’ and ‘powerhouse’ in the carcinogenesis of OSCC [23,56-59]. Increased levels of ROS in tumor cells are generated by altered metabolic activity, oncogene activation, and deregulated proliferation [60].…”
Section: Discussionsupporting
confidence: 73%
“…The TUNEL assay demonstrated that tumor cells do not undergo apoptosis and therefore, increased ROS generation by OXPHOS does not reach toxic levels. Based on our results and as currently stated by Whitaker-Menezes et al [57] in the context of breast cancer we assume that mitochondria are the ‘Achilles heel’ and ‘powerhouse’ in the carcinogenesis of OSCC [23,56-59]. Increased levels of ROS in tumor cells are generated by altered metabolic activity, oncogene activation, and deregulated proliferation [60].…”
Section: Discussionsupporting
confidence: 73%
“…So treatment completely inhibited the modest upregulation of glycolysis to meet ATP needs after FCCP treatment of MOSE-L cells. This has also been observed by other anti-cancer treatments and is thought to be associated with a toxic effect on cancer but not non-transformed cells [42]. This may be tissue specific since the suppression of respiration protects against apoptosis in muscle [43].…”
Section: Discussionmentioning
confidence: 84%
“…This understanding of the molecular mechanisms and implications of both mitochondrial pathways and glycolytic metabolism in cancer has fuelled an increase in research focusing on drugs that target both pathways [13]. Mito-carboxy proxyl (Mito-CP) – a five membered nitroxide (Figure 1) that is covalently linked to a lipophilic triphenylphosphonium cation is a mitochondria-targeted antioxidant.…”
Section: Introductionmentioning
confidence: 99%